The Effect of Cash Flow on Financial Distress through Profit Management (Study on State-Owned Companies) - Miftahul Khairat; Memen Suwandi; Namla Elfa Syariati (Academic Bright Collaboration, 2026)
Companies that experience financial stress often face a decline in the ability to generate cash flow. In this condition, management sometimes conducts profit management to improve the company's performance, which can affect the relationship between cash flow and the potential for financial distress. This study aims to examine the role of profit management as a variable that mediates the influence of operating cash flow and free cash flow on financial distress. The research used was qualitative with a comparative causal approach. State-owned companies listed on the IDX are used as research populations for the 2020-2023 period. The samples used amounted to 8 companies, then by using purposive sampling 32 samples were obtained that were ready to be observed. The research uses secondary data obtained from the annual financial statements of State-Owned Enterprises (SOEs) available through the official website of the Indonesia Stock Exchange. The findings of the study indicate that there is a direct influence of operating cash flow and free cash flow on financial distress. In addition, through profit management (intervening variables) there is an indirect influence between independent and dependent variables.